Lysozyme Imprinted poly(hydroxyethyl methacrylate) Cryogel Membrane with the Assistance of polydopamine - Aykut Arif Topçu (Hittite Journal of Science and Engineering, 2023)
The surface imprinted technique was utilized in creating the synthetic lysozyme receptors on the poly(hydroxyethyl methacrylate) [p(HEMA)] cryogel membrane with the assistance of polydopamine under alkaline conditions. Following the design of the artificial receptors, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and the swelling test were used for the characterization studies and the lysozyme adsorption capability of the adsorbent was evaluated in the aqueous solution.